Comparative outcomes for sclerotherapy of head and neck venous vascular malformation between alcohol and bleomycin - Dittapong Songsaeng (2018)
© 2015, Journal of the Medical Association of Thailand. All right reserved. Objective: To assess and compare the effectiveness of the two sclerosing agents (95% alcohol and Bleomycin) for the treatment of head and neck venous malformation (VM). Material and Method: The authors retrospectively reviewed our experience in treating VM of the head and neck region using two sclerosing agents, 95% alcohol (November 2001 to June 2008) and bleomycin (July 2008 to July 2010). Patients’ demography (age, sex), lesion number, location, type (focal/extensive), and characteristic features (cystic/tubular/mixed) were recorded. The treatment outcome was determined by decrease in size of VM in photographs taken at one month and at final clinical follow-up. These were analyzed by two radiologists using visual rating scale (worst or not improved, <50%, 50-75%, >75% of size reduction). One-way Anova test (p<0.1) was used to show the differences in treatment effectiveness of the two sclerosing agents at short- and long-term intervals. Results: Thirty-three patients, age ranged from 11 to 62 years (mean 25.1 years), with 27 female and six male patients were included in this study. The majority of patients were less than 16 years (17 patients, 51%). The 43 lesions were categorized as 28 VMs were focal (65.1%), 15 (34.9%) diffuse, and 30 (69.7%) were of the mixed type. Sixteen lesions were treated with 95% alcohol, 23 lesions with bleomycin, and four lesions with a combination of the two sclerosants. The range of number of procedures was 1 to 16 (mean 3.76 procedures per patient) for alcohol, and 1 to 5 (mean 2.27 procedures per patient) for bleomycin. The cumulative dose of sclerosant used was 101 ml for alcohol and 32.11 mg for bleomycin. Total follow-up at 1-month and at final was 43/43 (100%) and 35/43 (81.4%) respectively. Mean follow-up interval was 14.7 months. Differences in size reduction after treatment by different sclerosing agents were found. At more than 1-year follow-up, those treated with bleomycin gained graded 3 (>75%) size reduction more than treated by 95% alcohol. No VM treated with 95% alcohol obtained grade 3 of size reduction at 1-year follow-up. Multiple regression analysis showed VM’s favorable character for bleomycin treatment by decreasing mixed, cystic, and tubular. Pediatrics had relatively more benefit with bleomycin treatment. Conclusion: Sclerotherapy using either alcohol or bleomycin is an effective treatment for VMs. Different treatment outcomes were significant at long-term with group of VM those treated with bleomycin but not at short-term (p<0.1).